2017
DOI: 10.1080/00016357.2017.1392601
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of radiation on resorbable blast material titanium implants: an experimental study in rabbits

Abstract: Radiotherapy with 15 and 30 Gy doses can adversely affect osseointegration of implants by reducing the quality of bone and impairing the bone-to-implant contact. The mechanism of action seems to be related to alterations in Bmp-2 and Fgf-2 mRNA expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…The single dose of 30 Gy radiation was also used in a rabbit study that demonstrated a low volume of newly formed bone between the labels, which suggested that the rate of bone formation is slow. 11,12 The micro-CT results involved three microstructural parameters that are complementary and used to qualify cortical bone integrity and quality. The decrease in bone mass found in the irradiated groups of bone tissue both close and distant to the implant may have occurred due to the impairment of vascularization and osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The single dose of 30 Gy radiation was also used in a rabbit study that demonstrated a low volume of newly formed bone between the labels, which suggested that the rate of bone formation is slow. 11,12 The micro-CT results involved three microstructural parameters that are complementary and used to qualify cortical bone integrity and quality. The decrease in bone mass found in the irradiated groups of bone tissue both close and distant to the implant may have occurred due to the impairment of vascularization and osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both hind legs of each rabbit were subjected to irradiation using a single dose of 30 Gy. 11 , 12 , 17 A 5-mm bolus was given to ensure full build-up. The tibia metaphysis region of the hind leg was the designated zone for irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations